Fat provisioning in winter impairs egg production during the following spring: a landscape‐scale study of blue tits. (5th February 2013) - Plummer, Kate E.; Bearhop, Stuart; Leech, David I.; Chamberlain, Dan E.; Blount, Jonathan D.
Summary: Provisioning of garden birds is a growing phenomenon, particularly during winter, but there is little empirical evidence of its true ecological impacts. One possibility is that winter provisioning could enhance subsequent breeding performance, but this seems likely to depend on the types of nutrients provided. For example, whereas effects of macronutrients such as fat are unlikely to be carried over to influence breeding in small passerines, micronutrients such as dietary vitamin E (an antioxidant) may be stored or have lasting health benefits. Here, we examine the carry‐over effects of winter food supplements on egg production in wild populations of blue tits ( Cyanistes caeruleus ). Over three consecutive years, birds were provisioned with fat, fat plus vitamin E or remained unfed (controls). The provision of fat in winter resulted in smaller relative yolk mass in larger eggs and reduced yolk carotenoid concentrations in early breeders. However, these effects were not seen in birds provisioned with fat plus vitamin E. Lay date, clutch size, egg mass and yolk vitamin E concentrations were not significantly affected by winter provisioning treatment. Our results indicate that winter provisioning can have important downstream consequences, in particular affecting investment in egg production several weeks or months later. Provisioning is widely applied to support garden bird populations and for the conservation management of endangered species. However, our results challenge the assumption that such practices are always beneficial at the population level and emphasize how the ecological impacts can depend on the specific nutritional profile of provisioned foods. Abstract : Provisioning of food to wild birds is widespread but its ecological impacts are poorly understood. The authors show that winter provisioning with fat results in smaller relative yolk mass and reduced yolk carotenoid concentrations in early breeders, while these effects are not seen in birds provisioned with fat‐plus‐vitamin E. The results highlight how the ecological impacts of provisioning can depend on the nutritional profile of foods.